Coping espiritual/religioso e qualidade de vida da pessoa com lesão medular - Meira Neto, Antônio (2021)
Coping is a common action among human beings, directly linked to stresses caused by events related to the satisfaction or frustration of human desires, which makes them try to adapt as best as possible to difficult situations. Religious coping is defined as the action of understanding and dealing with stressors based on religious/spiritual strategies in response to the stressor and suffering. The aim of the study is to analyze the relationship between spiritual/religious coping and the quality of life of people with spinal cord injury. 95 people participated in the study at levels from C-5 to S-1 participated in the study, witch could be in the hospitalization phase or not. Data collection took place through questionnaires on sociodemographic and injury information, the SRCOPE-14 scale and the WHOQOL-BREF, and took place from August 2020 to October 2021. A survey was also carried out in the literature to indetify works related to the influence of spiritual/religius coping on quality of life. To analyze the comparison of results, the Kolmogorov-Smirnov test was chosen. The hypothesis raised was that patients with higher scores on positive spiritual/religious coping would also score higher on quality of life. The results found showed a negative and significant correlation between negative spiritual/religious coping and psychological well-being. It is concluded that the greater the use of negative spiritual/religious coping, the lower the psychological well-being of people with spinal cord injury. It was concluded that psychological well being is negatively related to negative spiritual/religious coping.